Tegami bachi letter bee Volume 11, A bee's bag - Asada, Hiroyuki, 1968-; Amtower, Rich (Viz Media, 2012)
"Largo Lloyd, ousted director of the Beehive, saves the life of a Marauder-- and, in return, demands to be taken to the leader of Reverse. Will the Letter Bees finally penetrate to the heart of the rebel organization? Meanwhile, with his hero Gauche returning home at last, things are looking up for Lag-- until he discovers the shocking truth about Gauche!" -- p. [4] of cover.